1987
DOI: 10.1080/00288330.1987.9516194
|View full text |Cite
|
Sign up to set email alerts
|

Coastal fishes of the Kermadec Islands

Abstract: Fishes were observed and collected at the Kermadec Islands in 1984 and 1985. Five families and 16 species were newly recorded from the New Zealand region and a further 18 species were newly recorded from the Kermadec Islands. The number of coastal fishes known from the Kermadec Islands is now 112. Seventy-seven coastal fish species were classified into five abundance classes at five Kermadec Islands localities; 27 showed north-south abundance trends. Of the 112 Kermadec Islands species, 55% are found in temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 8 publications
1
41
1
Order By: Relevance
“…Francis et al (1987) have shown that those reports were based on misidentifications of the recently described and morphologically similar P. kermadecensis (though Allen (1987) was apparently unaware of the reports and did not include them in the synonymy of P. kermadecensis). The discovery of two specimens of /".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Francis et al (1987) have shown that those reports were based on misidentifications of the recently described and morphologically similar P. kermadecensis (though Allen (1987) was apparently unaware of the reports and did not include them in the synonymy of P. kermadecensis). The discovery of two specimens of /".…”
Section: Discussionmentioning
confidence: 99%
“…Parma kermadecensis is endemic to the Kermadec Islands, where it is common to abundant (Allen 1987;Francis et al 1987). Parma polylepis Gunther, 1862 was reported from the Kermadec Islands by Paulin & Stewart (1985) and Schiel et al (1986), but their reports were based on misidentified P. kermadecensis (Francis et al 1987). Therefore there are currently no valid reports of P. polylepis from New Zealand waters.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…5, inset). Francis et al (1987) reported that the species increased in abundance from south to north through the Kermadec Islands, with none seen at L'Esperance and Havre Rocks, but schools seen at least occasionally at Cheeseman, Curtis, Macauley, Haszard, Raoul, and Meyer Islands. Outside New Zealand, the species is recorded from Norfolk and Lord Howe Islands, and has a disjunct distribution on the eastern and western coasts of Australia.…”
Section: Distributionmentioning
confidence: 99%